Epileptiform discharges in neurodegenerative diseases linked to atrophy but not associated with iron depositions - Christian Sandøe Musaeus; Kristian Steen Frederiksen; Gunhild Waldemar; Troels Wesenberg Kjær; Mark B. Vestergaard; Birgitte Bo Andersen; Peter Høgh; Steen Gregers Hasselbalch; Preben Kidmose; Martin Christian Hemmsen; Mike Lind Rank; Henrik Bo Wiberg Larsson; et al. (GeroScience, 2026)
Epileptiform discharges in Alzheimer’s disease (AD) and Lewy body dementia (DLB) may be associated with cognitive decline. Iron accumulation has been implicated in neurodegenerative processes; however, its relationship to epileptiform discharges remains unknown. In addition, the relationship between iron deposition, structural brain changes, and epileptiform discharges remains unclear. The objective is to investigate whether iron deposition and structural brain atrophy are associated with epileptiform discharges in patients with AD, DLB, and healthy controls (HCs). A total of 25 patients with AD, 10 patients with DLB, and 15 HCs were included in the analysis. The participants underwent MRI including quantitative susceptibility mapping (QSM) and structural T1-weighted imaging. We examined the four regions of interest, which are tied to iron deposition and AD pathology. Ear-EEG recordings were used to quantify spike frequency (epileptiform discharges/24 h). No significant group differences were found for susceptibility across regions. Susceptibility was not associated with spike frequency. Patients with AD exhibited significant hippocampal atrophy. Higher hippocampal volume was associated with lower spike rates in adjusted models. Susceptibility and hippocampal volume were associated, and in a multilinear model with age, hippocampal volume accounted for a larger proportion of the explained variance. This study found no evidence linking iron deposition to epileptiform discharges in AD or DLB. Instead, hippocampal atrophy appears more strongly associated with epileptiform discharges, which could indicate that the underlying pathological processes rather than iron are the primary driving factor for epileptiform discharges.

Normal cerebral oxygen consumption and lactate levels in patients with Alzheimer’s disease and Lewy body dementia - Christian Sandøe Musaeus; Gunhild Waldemar; Troels Wesenberg Kjær; Birgitte Bo Andersen; Peter Høgh; Steen Gregers Hasselbalch; Ulrich Lindberg; Kristian Steen Frederiksen; Henrik Bo Wiberg Larsson; Mark B. Vestergaard (GeroScience, 2025)
Brain metabolism is reduced in patients with dementia disorders, as demonstrated by hypometabolism on 2-deoxy-2-[ 18 F]fluoroglucose ([ 18 F]FDG) positron emissions tomography. A contributing factor to the hypometabolism could be decreased cerebral blood flow (CBF) leading to a state of subtle hypoperfusion‐induced tissue hypoxia causing a reduced brain oxygen metabolism and consequently elevated brain lactate. In the current exploratory study, we investigated brain lactate, global and regional CBF, and global cerebral metabolic rate of oxygen (CMRO 2 ) in patients with Alzheimer’s disease (AD) and dementia with Lewy bodies (DLBs). We hypothesized that the patients demonstrate a state of tissue hypoxia with reduced CMRO 2 and elevated brain lactate concentration. Participants included 24 AD patients, 10 DLB patients, and 15 healthy controls. MR spectroscopy measured lactate in the precuneus and occipital lobe. Global CBF and venous oxygen saturation (for CMRO2 calculation) were assessed using phase-contrast and susceptibility-based oximetry MRI, respectively. Regional CBF was measured with ASL-MRI. We observed no significant difference in either brain lactate or CMRO 2 between groups. The regional CBF in precuneus was significantly lower in AD compared to HC; however, this hypoperfusion was not associated with a higher lactate concentration. The lack of a difference in CMRO 2 or lactate concentration between patients and controls suggests that the hypometabolism observed in patients with AD and DLB may reflect structural neurodegeneration and not a state of tissue hypoxia. The local decrease of CBF in precuneus in patients with AD may be due to a lower CBF demand due to neurodegeneration.

Neonatal domoic acid alters in vivo binding of [11C]yohimbine to α2-adrenoceptors in adult rat brain - Majken B. Thomsen; Thea P. Lillethorup; Steen Jakobsen; Erik H. Nielsen; Mette Simonsen; Gregers Wegener; Anne M. Landau; R. Andrew Tasker (Psychopharmacology, 2016)

Chronic treatment with the phosphodiesterase type 5 inhibitors sildenafil and tadalafil display anxiolytic effects in Flinders Sensitive Line rats - Nico Liebenberg; Brian H. Harvey; Linda Brand; Gregers Wegener; Christiaan B. Brink (Metabolic Brain Disease, 2012)

[11C]Mirtazapine binding in depressed antidepressant nonresponders studied by PET neuroimaging - Donald F. Smith; Bo S. Stork; Gregers Wegener; Mahmoud Ashkanian; Steen Jakobsen; Dirk Bender; Hélène Audrain; Karina H. Vase; Søren B. Hansen; Poul Videbech; Raben Rosenberg (Psychopharmacology, 2009)

Receptor occupancy of mirtazapine determined by PET in healthy volunteers - Donald F. Smith; Bo S. Stork; Gregers Wegener; Steen Jakobsen; Dirk Bender; Hélène Audrain; Svend B. Jensen; Søren B. Hansen; Anders Rodell; Raben Rosenberg (Psychopharmacology, 2007)

Granulocyte-colony stimulating factor in the prevention of postoperative infectious complications and sub-optimal recovery from operation in patients with colorectal cancer and increased preoperative risk (ASA 3 and 4)¶ Protocol of a controlled clinical trial developed by consensus of an international study group¶ Part three: individual patient, complication algorithm and quality management¶ - B. Stinner; A. Bauhofer; W. Lorenz; M. Rothmund; U. Plaul; A. Torossian; I. Celik; H. Sitter; M. Koller; A. Black; D. Duda; A. Encke; et al. (Inflammation Research, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Hypertonic cell shrinkage reduces the K + conductance of rat colonic crypts - B. Weyand; R. Warth; M. Bleich; D. Kerstan; R. Nitschke; R. Greger (Pflügers Archiv - European Journal of Physiology, 1998)

The basolateral Ca 2+ -dependent K + channel in rat colonic crypt cells - M. S. Nielsen; R. Warth; M. Bleich; B. Weyand; R. Greger (Pflügers Archiv - European Journal of Physiology, 1997)

MAO-A inhibition in brain after dosing with esuprone, moclobemide and placebo in healthy volunteers: in vivo studies with positron emission tomography - M. Bergström; G. Westerberg; G. Németh; M. Traut; G. Gross; G. Greger; H. Müller-Peltzer; A. Safer; S.-Å. Eckernäs; A. Grahnér; B. Långström (European Journal of Clinical Pharmacology, 1997)